2007
DOI: 10.1103/physrevd.75.105022
|View full text |Cite
|
Sign up to set email alerts
|

Full twisted Poincaré symmetry and quantum field theory on Moyal-Weyl spaces

Abstract: We explore some general consequences of a proper, full enforcement of the "twisted Poincaré" covariance of Chaichian et al [14], Wess [52], Koch et al [35], Oeckl [43] upon many-particle quantum mechanics and field quantization on a Moyal-Weyl noncommutative space(time). This entails the associated braided tensor product with an involutive braiding (or ⋆-tensor product in the parlance of Aschieri et al [3,4]) prescription for any coordinates pair of x, y generating two different copies of the space(time); the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
237
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(263 citation statements)
references
References 57 publications
(168 reference statements)
20
237
2
4
Order By: Relevance
“…IV͒. Lacking such a rule, they suggested 6 to replace it by a condition imposed on the Wightman functions. This condition formally looked the same as that in the commutative case.…”
Section: Conclusion Comments and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…IV͒. Lacking such a rule, they suggested 6 to replace it by a condition imposed on the Wightman functions. This condition formally looked the same as that in the commutative case.…”
Section: Conclusion Comments and Outlookmentioning
confidence: 99%
“…For example, there was a lengthy discussion in Ref. 6 on the need of formulating a transformation rule of fields under the twisted Poincaré algebra, but the authors did not directly address the issue, rather they suggested a way to side step it instead. Also, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…in quantum-covariant NC field theory [63][64][65]. For quantum twist deformations of enveloping Lie algebras U(g) (g = o(4; C), o(4 − k, k) (k = 0, 1, 2), and o * (4) = 0(2; H)); for o(4; C) (see section 5.1, 5.2) the algebra of quantum modules, describing e.g.…”
Section: Jhep11(2017)187mentioning
confidence: 99%
“…Мы не затронули здесь твистованную пуанкаре-ковариантность, но следует отметить, что наивное сочетание рассмотренной выше деформации с такой 428 М. А. СОЛОВЬЕВ ковариантностью может привести к теории, которая физически эквивалентна неде-формированной, аналогично теории, обсуждавшейся в работе [20]. Вопрос о том, как наилучшим образом объединить идею пространственно-временной некоммута-тивности с основными принципами квантовой физики, пока остается открытым.…”
Section: θ-локальностьunclassified